The Potential Utilization of Blockchain Technology - Untung Rahardja; Ninda Lutfiani; Qurotul Aini; Isabella Yaumil Annisa (Blockchain Frontier Technology, 2021)
The application of blockchain innovation in E-commerce has a benefit. Add a space be the need for closeness sense in carrying out the transaction process in a security framework is required to preserve the privacy of information. One of the technological marvels is a Blockchain. The application of Blockchain innovation is to supply security for certificate security within the computerized period 4.0 so as not to control by unreliable parties. By utilizing the strategy of issue detailing, inquire about the plan, information, information preparing & introduction, examination & research reports and investigate strategies seven writing ponders. The application of blockchain innovation in an E-commerce service may be a need for closeness sense in carrying out the exchange handle a security framework is required to preserve information secrecy. Numerous things are valuable in Blockchain innovation, counting observing monetary resources, wellbeing records, character, and planning the supply chain. However, many proposals lack criticism and have static thinking. So that it fails to get the main benefits of the blockchain.